Interleukin 2 is an Upstream Regulator of CD4+ T Cells From Visceral Leishmaniasis Patients With Therapeutic Potential. (23rd February 2019) - Chauhan, Shashi Bhushan; Faleiro, Rebecca; Kumar, Rajiv; Ng, Susanna; Singh, Bhawana; Singh, Om Prakash; Singh, Siddharth Sankar; Amante, Fiona; Rivera, Fabian de Labastida; Rai, Madhukar; Chakravarty, Jaya; Sacks, David; et al.
Abstract: Control of visceral leishmaniasis (VL) caused by Leishmania donovani requires interferon-γ production by CD4 + T cells. In VL patients, antiparasitic CD4 + T-cell responses are ineffective for unknown reasons. In this study, we measured the expression of genes associated with various immune functions in these cells from VL patients and compared them to CD4 + T cells from the same patients after drug treatment and from endemic controls. We found reduced GATA3, RORC, and FOXP3 gene expression in CD4 + T cells of VL patients, associated with reduced Th2, Th17, and FOXP3 + CD4 + T regulatory cell frequencies in VL patient blood. Interleukin 2 (IL-2) was an important upstream regulator of CD4 + T cells from VL patients, and functional studies demonstrated the therapeutic potential of IL-2 for improving antiparasitic immunity. Together, these results provide new insights into the characteristics of CD4 + T cells from VL patients that can be used to improve antiparasitic immune responses. Abstract : Transcriptional changes in CD4 + T cells during visceral leishmaniasis caused by Leishmania donovani infection were examined, and interleukin 2 (IL-2) was identified as an important upstream regulator of these cells. Functional studies demonstrated the therapeutic potential of IL-2 for improving antiparasitic immunity.